Role of β-isomerized C-terminal telopeptides (β-CTx) and total procollagen type 1 amino-terminal propeptide (tP1NP) as osteosarcoma biomarkers - Hu, Tu (Int J Clin Exp Med, 2015)
Introduction: Few serum markers are valid and useful for the diagnosis or therapeutic effect monitoring of osteosarcoma. This study aimed to investigate the role of β-isomerized C-terminal telopeptides (β-CTx) and total procollagen type 1 amino-terminal propeptide (tP1NP) as serological biomarkers for osteosarcoma patients. Materials and Methods: A total of 48 patients with osteosarcoma and 55 healthy volunteers were investigated. Serum β-CTx and tP1NP levels were measured by electrochemiluminescence immunoassay. Data were analyzed by t test with Walth’s correction and receiver operating characteristic (ROC) curve analysis. Results: The baseline levels of β-CTx and tP1NP were found to be significantly higher in patients with osteosarcoma than the healthy volunteers. The mean areas under the ROC curves were 0.919 (range, 0.864-0.973) for β-CTx and 0.866 (range, 0.792-0.939) for tP1NP. The levels of β-CTx and tP1NP were lower in patients with stable disease after operation than those before operation. Conclusion: These findings support our hypothesis that β-CTx and tP1NP are promising serum biomarkers for diagnosing or monitoring osteosarcoma.